A new species of the genus Decussobates Cook, 1988 from Argentina, with the first description of the male (Acari: Hydrachnidia: Hygrobatidae) - Smit, Harry (Zootaxa, 2018)
In 1988 Cook described the hygrobatid genus Decussobates from Chile (Cook 1988). The description was based on females only. He described two species of the genus. A new record of the genus from southern Argentina, including males, necessitates an emendation of the description of the genus. The new material from Argentina belongs to a new species, which will be described below.